RANCANG BANGUN SISTEM INFORMASI MANAJEMEN APOTEK CEMARA - Hidayani, Nurul (Jurusan Informatika Universitas Tanjungpura, 2015)
Abstrack- Cemara drugstore has been managing drugs sales transactions and monthly reports manually that takes a long time in operational. This problem can be solved by developing drugstore information system management. The System is implemented by using a PHP programming and database MySQL. The function of drugstore information system management is to manage the drugstore in recording drug sales transaction, drug purchases transaction, returns transaction, addition of drug data, addition of employeers, addition of supplier data, addition of doctor data, addition of physician data and composing monthly reports. The drugstore information system management and database make the managements control easier in Cemara drugstore. By testing calculations using a borang that is measured with Likert's scale Summated Rating (LSR) produce a level of success with a percentage of 98.33% on SIMANTEK implemented in Cemara drugstore.Â